Dyslexia in the University. Guidelines for inclusion and teaching of the University of Florence - Zappaterra, Tamara (Education Sciences & Society - Open Access, 2016)
This paper reports the results of an interdisciplinary project (pedagogical, medical, engineering area) of the Centre for Research on Disability Issues, operating within the University of Florence, which provides support for students with disabilities and with Learning Disorders (LD). The project, which aims at drawing up a protocol for the inclusion and learning support for students with learning difficulties, after a first reconnaissance of user needs that have been reached with the participation of the very same protagonists (thanks to a questionnaire built on purpose and a series of focus groups) is now at the stage of guidelines drafting for inclusion and education, to be used by teachers, students and administrative staff. In the article, after a brief summary of the previous phases of the project, the reader can find the most significant elements of the guidelines for teaching, i.e. the section for teachers, whose aim is to implement a LD-friendly teaching, even at the university level, in compliance with Law 170/2010. Keywords learning disabilities; inclusive education; special education needs; didactic tools; university